RESPON AMERIKA SERIKAT ATAS SERANGAN SENJATA KIMIA SURIAH DI KHAN SHEIKHOUN: ANALISIS SISTEM INTERNASIONAL - Wicaksono, Stefanus Ari; Amrina, Ulli; Andrian, Fressy; Akse, Bernadeta Andela; Adriani, Evilita (Global and Policy Journal of International Relations, 2018)
ABSTRACTSyria's chemical weapons attack in the city of Khan Sheikoun on April 4, 2017 became the center of international attention. Unlike other countries that only limited to condemn and condemn, the United States responded to the government action of the regime of Bassar al Assad by attacking the Syrian military base using 59 missiles tomhawk.Penulis using the level of international system analysis with specific to Morton Kaplan's universal system exploration as a tool to analyze the US action. From the results of research that has been done by the author, that the US apply so to Syria because terstimulus by the international system at that time that the UN is perceived not enough to suppress the ownership of chemical weapons belonging to government Bassar al Assad.Keywords: United States, United Nations (UN), Syria chemical weaponDOI: https://doi.org/10.33005/jgp.v6i01.1883